Promotion Effectiveness Using EPIC Model - Alexius Endy Budianto (MBR (Management and Business Review), 2017)
Competition between universities and the amount of expenditure funds that require the college to know the effectiveness of promotional activities that have been done. This study aims to determine the effectiveness of promoting the introduction of campus "Go to School" using EPIC model Universitas Kanjuruhan Malang. Sampling technique using simple random sampling. Respondents in this study are undergraduate students Faculty of Science and Technology Universitas Kanjuruhan Malang active until 2015/2016 academic year as many as 97 students. This research uses EPIC Model analysis method. The results showed that the dimension of empathy is effective, the dimension of persuasion is quite effective. Dimensional impact is quite effective as for the dimensions of communication is quite effective